2017
DOI: 10.1155/2017/6829510
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and Failure Characteristics of Self-Compacting Concrete Containing Recycled Waste Glass Aggregate

Abstract: The effects of different proportions of green-colored waste glass (WG) cullet on the mechanical and fracture properties of selfcompacting concrete (SCC) were experimentally investigated. Waste bottles were collected, washed, crushed, and sieved to prepare the cullet used in this study. Cullet was incorporated at different percentages (0%, 20%, 40%, 60%, 80%, and 100% by weight) instead of natural fine aggregate (NFA) and/or natural coarse aggregate (NCA). Three SCC series were designed with a constant slump fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…(7) Reduction in the w/c ratio enhances the strength due to decline in free water available as long as enough water is available for proper hydration reaction. (8) It is recommended to use copper slag as fine aggregate in concrete up to 70% substitution level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(7) Reduction in the w/c ratio enhances the strength due to decline in free water available as long as enough water is available for proper hydration reaction. (8) It is recommended to use copper slag as fine aggregate in concrete up to 70% substitution level.…”
Section: Resultsmentioning
confidence: 99%
“…Tripathi and Chaudhary [7] tested the feasibility of utilizing imperial smelting furnace slag in concrete. Al-Bawi et al [8] have investigated the strength attributes of the concrete comprising recycled glass as a sand substitute.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in the previous section of this study, self-compacting materials in theory are materials in which the difference in porosity ratio in the densest and weakest state is small. e experiments of this study were performed similar to the standard experiments of ASTM (D-4253-93 and D-4254-91) [12,13] because, with the help of these experiments, the maximum and minimum porosity ratios can be calculated. erefore, in this study, loose and dense porosity ratios are investigated in this way.…”
Section: Selection Of Tests and Materialsmentioning
confidence: 99%
“…In 2002, a study was conducted at the University of Tokyo, Japan, on the ratio of maximum and minimum porosity of materials under ideal conditions and in real life [4]. With the help of mathematical relations, the maximum porosity ratio and the minimum porosity ratio of the ideal materials were calculated equally [13]. ey concluded that the maximum and minimum porosity ratios as well as the "maximum and minimum porosity ratio difference" depend on the grain size, grain size curve, and fine grain percentage [4] (Figure 3).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, industrial waste such as coal ash, iron waste, smelting furnace slag, recycled glass etc. have been used as substitute to NFA in the concrete (Onprom et al 2015, Ghafoori et al 1996, Aggarwal et al 2007, Andrade et al 2009, Bai et al 2005, Zhu et al 2015, Tripathi et al 2016, Al-Bawi et al 2017. CS is one such industrial waste generated during the production of the copper.…”
Section: Introductionmentioning
confidence: 99%